Defeitos topológicos, energia escura e mundo brana - Nunes, João Victor Queiroga (2019)
This dissertation deals with models in real scalar fields theory, general relativity, dark energy and branes modeled by topological defects with real scalar fields. For this purpose, we firstly work on a review about real scalar field theory, topological and nontopological defects in (1,1) dimensions with standard and generalized dynamics. Then, an introduction of cosmology is done passing by topics like general relativity, metric perturbations and dark energy in the standard model, for one and two scalar fields, and the tachyonic model. Lastly, we use the methods developed so far to study braneworld scenarios, their applications in physical phenomena and theoretical results under the real scalar fields perspective.